Characterization of the antioxidative polysaccharides from Ziziphus jujube cv. Goutouzao and its tumor‐inhibitory effects on human colorectal carcinoma LoVo cells via immunocyte activation. Issue 11 (21st September 2020) - Liang, Qian; Wang, Xingyu; Yang, Shuo; Yu, Linhong; Gao, Qiaohui; Yang, Xingbin; Zhao, Yan
Abstract: Colorectal cancer, the most common malignancy in Asian and west world, is listed as the fourth lethal neoplastic disease with increasing incidence worldwide. Recently, Ziziphus jujube were reported with hepatoprotective, antihypertensive, and hypoglycemic functions. The polysaccharides from Ziziphus jujube was considered as the main component for these bioactivities. In this study, polysaccharides from Ziziphus jujube cv. Goutouzao (GZSP) was comprehensively investigated, and characterized as a heteropolysaccharide with antioxidant activity. Besides, it can stimulate the viability of immune cells RAW 264.7, which in turn inhibited the proliferation of colorectal carcinoma cells (LoVo) by inducing apoptosis, arresting cell cycle in G0/G1, and increasing intracellular ROS, as demonstrated by Flow Cytometric analyses. The results suggest that, different from chemotherapeutic modalities, GZSP can exert antitumor effects by activating immune reaction, providing more evidence for the development of GZSP‐based functional foods and anticancer drugs serving as human colon cancer prevention. Practical applications: Natural products from medicinal and edible plant are great sources of phytochemicals beneficial to human health, such as tea polyphenols, carotenoids, and phytosterols, etc. In this study, GZSP, the polysaccharides from a well‐received fruit, Ziziphus jujube cv. Goutouzao, has been comprehensively investigated. The results show that GZSP fights against free radicals commonly found in human circulation, a property that enables it to be used as an antioxidant food additive with jujube flavor. More importantly, GZSP impedes neoplastic progression by activating immune response, as evidenced by the inhibition of colorectal carcinoma (LoVo) cells. Comparing with chemotherapies usually imposing cytotoxicity on normal tissues, natural product GZSP is able to exert the antiproliferative effects on carcinoma cells with minimal side‐effects. Therefore, GZSP‐based functional foods and anticancer drugs with the purpose of preventing human colon cancer formation are promising to be developed. Abstract : Polysaccharide from Ziziphus jujube cv. Goutouzao (GZSP) was a glucose‐rich heteropolysaccharide. GZSP exerts an antioxidant effects by scavenging free radicals commonly. GZSP fights against proliferation of colorectal carcinoma cells by activating immune responses.